Bipedality and hair loss in human evolution revisited: The impact of altitude and activity scheduling. Issue 94 (May 2016) - Dávid-Barrett, Tamás; Dunbar, Robin I.M.
Abstract: Bipedality evolved early in hominin evolution, and at some point was associated with hair loss over most of the body. One classic explanation (Wheeler 1984: J. Hum. Evol. 13, 91–98) was that these traits evolved to reduce heat overload when australopiths were foraging in more open tropical habitats where they were exposed to the direct effects of sunlight at midday. A recent critique of this model (Ruxton & Wilkinson 2011a: Proc. Natl. Acad. Sci. USA 108, 20965-20969) argued that it ignored the endogenous costs of heat generated by locomotion, and concluded that only hair loss provided a significant reduction in heat load. We add two crucial corrections to this model (the altitude at which australopiths actually lived and activity scheduling) and show that when these are included there are substantial reductions in heat load for bipedal locomotion even for furred animals. In addition, we add one further consideration to the model: we extend the analysis across the full 24 h day, and show that fur loss could not have evolved until much later because of the thermoregulatory costs this would have incurred at the altitudes where australopiths actually lived. Fur loss is most likely associated with the exploitation of open habitats at much lower altitudes at a much later date by the genus Homo .